PERKEMBANGAN BAHASA MELALUI METODE BERNYANYI DALAM KEGIATAN MENGENAL HURUF PADA ANAK USIA 5 - 6 TAHUN DI TK NURUL IMAN DESA TONU JAYA KECAMATAN HUAMUAL BELAKANG KABUPATEN SERAM BAGIAN BARAT - Firna Ramdin; Abarua; Junita. L. Kundre (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examined whether the singing method could improve language development through letter recognition activities for children aged 5-6 years at Nurul Iman Kindergarten, Tonu Jaya Village, Huamual Belakang District, West Seram Regency. The research employed classroom action research methodology conducted over two cycles, with each cycle comprising planning, implementation, observation, and reflection phases. The study involved 31 children (20 boys and 11 girls) from Nurul Iman Kindergarten. Results indicated significant improvement in language development through letter recognition activities using the singing method. In the first cycle, children's language abilities were categorized as follows: 10 children (32.2%) not yet developed (BB), 5 children (16.1%) beginning to develop (MB), 7 children (22.5%) developing as expected (BSH), and 9 children (29.03%) very well developed (BSB). By the second cycle, improvement was evident with 7 children (22.5%) beginning to develop (MB), 9 children (29.03%) developing as expected (BSH), and 15 children (48.38%) very well developed (BSB). The findings demonstrate that the singing method effectively enhanced language development in letter recognition activities, with a notable increase in children achieving very good development from 29.03% to 48.38%. This research concluded that the singing method is an effective approach for improving language development through letter recognition activities for children aged 5-6 years.